All-optical network enabling technologies - Yiran MA; LARKEI C (Dianxin kexue)
As one of the most important parts of all-optical networks,ROADM brings benefits such as flexibility,low-power consumption,cost and efficient utilization of network resources.Consequently they have been deployed in volume over recent years in backbone and metro networks.The WSS,the key component of the ROADM,was described,followed by a description of the features and challenges of next generation WSS designs.Finally,the CDC ROADM,which was the likely next evolutionary step for the ROADM,was investigated along will the necessary components development.